2016
DOI: 10.1158/1078-0432.ccr-16-0372
|View full text |Cite
|
Sign up to set email alerts
|

Unplugging JAK/STAT in Chronic Myelomonocytic Leukemia

Abstract: The proliferative component of chronic myelomonocytic leukemia, related to an increased sensitivity of myeloid progenitors to granulocyte macrophage–colony stimulating factor, suggests dedicated therapeutic approaches. In this issue, ruxolitinib, a JAK1 and -2 inhibitory drug, is shown to induce objective responses in chronic myelomonocytic leukemia patients. Clin Cancer Res; 22(15); 3707–9. ©2016 AACR. See related article by Padron et al., p. 3746

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…87,88 Therapeutic approaches targeting this signaling pathway are currently being assessed, 89 including the use of ruxolitinib that could control inflammatory symptoms (Table 3). 90 Extramedullary disease MPN-CMML patients can experience constitutional symptoms, including fatigue, diffuse bone pain, and night sweats, and develop a splenomegaly (;30% of cases), which is occasionally troublesome, resulting from extramedullary hematopoiesis.…”
Section: Myeloproliferative Cmmlmentioning
confidence: 99%
“…87,88 Therapeutic approaches targeting this signaling pathway are currently being assessed, 89 including the use of ruxolitinib that could control inflammatory symptoms (Table 3). 90 Extramedullary disease MPN-CMML patients can experience constitutional symptoms, including fatigue, diffuse bone pain, and night sweats, and develop a splenomegaly (;30% of cases), which is occasionally troublesome, resulting from extramedullary hematopoiesis.…”
Section: Myeloproliferative Cmmlmentioning
confidence: 99%
“…Previous studies have shown that the JAK-STAT signaling pathway is an important cascade mediating the effects of a wide range of cytokines such as transforming growth factor beta (TGF-β) [ 9 , 10 ], platelet-derived growth factor (PDGF) [ 11 ], interleukin (IL) 6 [ 12 ], and granulocyte colony-stimulating growth factor (G-CSF) [ 13 ]. Blocking the effects of these cytokines leads to a decrease in collagen synthesis, suppression of the proliferation of smooth muscle cells, fibroblasts, endotheliocytes, and an anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%
“…В ранее проведенных исследованиях было показано, что JAK-STAT-сигнальный путь является важным каскадом, опосредующим эффекты широкого спектра цитокинов, таких как TGF-β [4, 5], тромбоцитарного фактора роста (PDGF) [6], интерлейкина (ИЛ) 6 [7], гранулоцитарного колониестимулирующего фактора роста (G-CSF) [8]. Блокирование эффектов этих цитокинов приводит к снижению синтеза коллагена, подавлению пролиферации гладкомышечных клеток, фибробластов, эндотелиоцитов, противовоспалительному эффекту.…”
Section: Introductionunclassified